2022
DOI: 10.1111/bcp.15448
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing trend of tapentadol in a Sydney local health district

Abstract: Aims Tapentadol, an opioid with mu‐opioid receptor agonism and noradrenaline reuptake inhibition, has been increasingly used in Australia since 2011. However, data on hospital prescribing trends and indications are scarce. This study aimed to investigate hospital prescribing trends of tapentadol, oxycodone and tramadol in a Sydney local health district (LHD) and the indications for tapentadol hospital prescriptions in an Australian tertiary hospital. Methods We analysed 5‐year patient dispensing for tapentadol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…Compared with full opioid agonists such as oxycodone, the lower mu-opioid receptor activation of tapentadol required to provide comparable analgesia may be associated with fewer opioid-related side effects such as constipation [17]. In Australia, there have been recent rapid increases in tapentadol prescriptions [12,18], with tapentadol having the largest opioid market share by oral morphine equivalent (17.1%) in 2019 [19]; it is used more frequently than oxycodone in some hospital settings [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with full opioid agonists such as oxycodone, the lower mu-opioid receptor activation of tapentadol required to provide comparable analgesia may be associated with fewer opioid-related side effects such as constipation [17]. In Australia, there have been recent rapid increases in tapentadol prescriptions [12,18], with tapentadol having the largest opioid market share by oral morphine equivalent (17.1%) in 2019 [19]; it is used more frequently than oxycodone in some hospital settings [20].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with full opioid agonists such as oxycodone, the lower mu‐opioid receptor activation of tapentadol required to provide comparable analgesia may be associated with fewer opioid‐related side effects such as constipation [17]. In Australia, there have been recent rapid increases in tapentadol prescriptions [12, 18], with tapentadol having the largest opioid market share by oral morphine equivalent (17.1%) in 2019 [19]; it is used more frequently than oxycodone in some hospital settings [20]. Despite its contemporary uptake in Australia, there are fewer studies which capture its use on longer‐term side effects, as tapentadol use commenced less than a decade ago and, to our knowledge, there have been no studies separately analysing surgical patients discharged with tapentadol for the outcome of persistent postoperative opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 It has been recently reported that tapentadol has replaced oxycodone and tramadol to become the most frequently prescribed oral opioid prescribed in an Australian local health district. 28 Similarly, equivalence of oral oxycodone and tramadol has also been concluded. 29 Previous studies had demonstrated wide variations in the practice of opioid prescription on discharge.…”
Section: Discussionmentioning
confidence: 92%
“…Tramadol overdose had the highest incidence of seizures and is also associated with serotonin toxicity 21 . Tapentadol is another important opioid, and recent data suggests it may soon become one of the most common opioids ingested in overdose 22,23 …”
Section: Discussionmentioning
confidence: 99%